Identifying Study of Factors Influencing the Motivation of Work on a Voluntary Worker at the Asahan District Health Center - Arif Fachrian (Jurnal Scientia, 2023)
This study aims to identify the factors that influence work motivation in volunteer labor at the Asahan District Health Center. According to Herzberg (Munandar, 2001) there are 9 factors that influence work motivation, namely intrinsic factors which include responsibility, progress, the work itself, achievements, recognition, and in terms of extrinsic factors which include administration and policies, salary, interpersonal relations , and working conditions. The population in this study totaled 68 people and all populations were samples from the study. This study used data collection using the Totally Sampling technique at 2 Community Health Centers in Asahan District. This type of research is quantitative research. The research instrument used is the Rating Scale. Based on the research results, it is known that the job challenge factor itself gives the biggest contribution, namely 13.69% and the smallest is administration and company policy, which is equal to 7.42%.